2021
DOI: 10.1016/j.vaccine.2021.04.006
|View full text |Cite
|
Sign up to set email alerts
|

The safety and immunogenicity of an inactivated SARS-CoV-2 vaccine in Chinese adults aged 18–59 years: A phase I randomized, double-blinded, controlled trial

Abstract: Background This study examined the safety and immunogenicity of an inactivated SARS-CoV-2 vaccine. Method In a phase I randomized, double-blinded, placebo-controlled trial involving 192 healthy adults 18–59 years old, two injections of three doses (50 EU, 100 EU, 150 EU) of an inactivated SARS-CoV-2 vaccine or placebo were administered intramuscularly at a 2- or 4-week interval. The safety and immunogenicity of the vaccine were evaluated. Results … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
49
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(54 citation statements)
references
References 18 publications
1
49
0
3
Order By: Relevance
“…The main detailed reasons for the decline of vaccination among those 145 unvaccinated subjects included the concern about the vaccine safety, decline by vaccination staff, pregnancy or lactation ( Table 5 ). Studies demonstrated that the inactivated COVID-19 vaccine is safe [ 2 , 4 , 35 , 36 ], which is also observed in the present survey ( Tables S1 and S2 ). Actually, the chronic diseases under controlled conditions, such as hypertension, diabetes mellitus, supplement of thyroid hormone and others, are not the contradiction of vaccination [ 37 , 38 ].…”
Section: Discussionsupporting
confidence: 88%
“…The main detailed reasons for the decline of vaccination among those 145 unvaccinated subjects included the concern about the vaccine safety, decline by vaccination staff, pregnancy or lactation ( Table 5 ). Studies demonstrated that the inactivated COVID-19 vaccine is safe [ 2 , 4 , 35 , 36 ], which is also observed in the present survey ( Tables S1 and S2 ). Actually, the chronic diseases under controlled conditions, such as hypertension, diabetes mellitus, supplement of thyroid hormone and others, are not the contradiction of vaccination [ 37 , 38 ].…”
Section: Discussionsupporting
confidence: 88%
“…Previous studies [ 12 , 13 , 16 20 ] have shown that the three immunization programs (0, 14 procedure, 0, 21 procedure or 0, 28 procedure) induce varying degrees of immune effect, but the optimal interval of injections remains unclear. Furthermore, there is lack of studies on the immunogenicity and safety of inactivated SARS-CoV-2 vaccine in high-risk occupational population.…”
Section: Introductionmentioning
confidence: 99%
“…In June 2021, Anvisa approved, under special conditions, limited importation of two COVID-19 vaccines: Covaxin [108,109] and Sputnik V. Covaxin is an immunizer BBV152, which is a whole-virion inactivated SARS-CoV-2 vaccine formulated with a Toll-like receptor 7/8 agonist molecule adsorbed to alum (Algel-IMDG) or alum (Algel). The Indian company Bharat Biotech, in collaboration with the National Institute of Virology and the Indian Council of Medical Research, produced this vaccine.…”
Section: Characteristics Of Available Vaccinesmentioning
confidence: 99%
“…The Indian company Bharat Biotech, in collaboration with the National Institute of Virology and the Indian Council of Medical Research, produced this vaccine. It was approved for clinical trials for clinical testing in June 2020, with phase I and II results released in December last year [108,109].…”
Section: Characteristics Of Available Vaccinesmentioning
confidence: 99%